Vulvovaginal graft-versus-host disease: a review. (2nd November 2019) - Jacobson, M.; Wong, J.; Li, A.; Wolfman, W. L.
Abstract: Hematopoietic cell transplantation (HCT) is associated with well-described gynecologic sequelae, including vulvovaginal graft-versus-host disease (GVHD). Vulvovaginal GVHD is a common complication of allogeneic HCT, but has been under-reported in the literature. Guidelines have been published only recently to recommend common terminology, treatment, and surveillance. This review summarizes the presentation, management, and surveillance aspects of vulvovaginal GVHD. We recommend a standardized referral between women undergoing HCT and an experienced gynecologist capable of managing this disease and treating sexual side effects.